A volumetric lysimeter system for use with puddled rice an its rotational crops (MAUSAM, 1982)
A volumetric lysimeter with provision for maintaining standing water or sub-surface water table at any desired level is described. Its use for measuring evapotranspiration losses of rice and its rotational, aerobic crops is detailed.